Strengthening Environmental Care Character through Contextual Approach in Science Learning - Juni Ratnasari; Kama Abdul Hakam; Mupid Hidayat; Aceng Kosasih (Jurnal Penelitian Pendidikan IPA, 2024)
Strengthening the character of environmental care is an important effort to ensure the survival of all creatures in the future. However, currently the awareness of the importance of protecting the environment is still low in society, and schools have a very important role in developing this environmental awareness character. Environmental sensitivity includes attitudes and measures to prevent environmental damage and repair damage that has occurred. The environment not only plays a vital role for human life but is also important in the context of education in schools, affecting student success. This study aims to evaluate the use of contextualised learning approach in strengthening environmental awareness character in junior high school students. The research method used literature analysis from secondary sources. The results show that the contextual learning approach has a positive impact on strengthening students' environmental care character, allowing them to link learning with practical applications in daily life. This approach is also in line with efforts to realise the ‘Merdeka Belajar’ initiative initiated by the Ministry of Education, contributing to the realisation of national education goals.